2017
DOI: 10.1111/jmg.12259
|View full text |Cite
|
Sign up to set email alerts
|

Formation and preservation of fresh lawsonite: Geothermobarometry of the North Makran Blueschists, southeast Iran

Abstract: A low‐grade metamorphic “Coloured Mélange” in North Makran (SE Iran) contains lenses and a large klippe of low temperature, lawsonite‐bearing blueschists formed during the Cretaceous closure of the Tethys Ocean. The largest blueschist outcrop is a >1,000 m thick coherent unit with metagabbros overlain by interlayered metabasalts and metavolcanoclastic rocks. Blueschist metamorphism is only incipient in coarse‐grained rocks, whereas finer grained, foliated samples show thorough metamorphic recrystallization. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 72 publications
2
32
0
Order By: Relevance
“…We simplified the pelitic composition by ignoring the minute amounts of Na, Ca, and Ti and assumed that the system is saturated in H 2 O (water) and SiO 2 (quartz; i.e., K2O‐FeO‐Fe2O3‐MgO‐Al2O3‐SiO2‐H2O system). The calculated misfit between modeled and measured mineral compositions (see Hunziker et al, , their Equation 1) is minimized for temperatures between 400 and 425°C. For an X value of ~0.62, the crossing of the Si‐in‐Phe (atoms per formula unit or apfu; see Table ) and Mg#‐in‐Cld isopleths at these temperatures occurs at P~1.2 and 1.6GPa, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…We simplified the pelitic composition by ignoring the minute amounts of Na, Ca, and Ti and assumed that the system is saturated in H 2 O (water) and SiO 2 (quartz; i.e., K2O‐FeO‐Fe2O3‐MgO‐Al2O3‐SiO2‐H2O system). The calculated misfit between modeled and measured mineral compositions (see Hunziker et al, , their Equation 1) is minimized for temperatures between 400 and 425°C. For an X value of ~0.62, the crossing of the Si‐in‐Phe (atoms per formula unit or apfu; see Table ) and Mg#‐in‐Cld isopleths at these temperatures occurs at P~1.2 and 1.6GPa, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…P ‐ T conditions of ~22–26 kbar and 490–520°C suggest subduction of the Cycladic continental margin to ~70–80 km depth, along a cool geothermal gradient of ~6–7°C/km. Other Tethyan HP‐LT terranes including Corsica, Elba, Western Turkey, Iran, and Oman record comparably cold geotherms (Brovarone et al, 2011; Davis, 2011; Davis & Whitney, 2006; Hunziker et al, 2017; Papeschi et al, 2020; Plunder et al, 2015, 2016; Ravna et al, 2010; Searle et al, 1994, 2004; Wang et al, 2019; Warren & Waters, 2006), suggesting similar processes occurred along strike at slightly different times.…”
Section: Discussionmentioning
confidence: 99%
“…Underplating was interpreted to be an important factor for wedge growth due to the emergence of a low-grade metamorphic antiformal stack in the very north of the accretionary wedge ( Fig. 10A; Hunziker et al, 2017). Grando and McClay (2007) showed that underplated sediments may form the footwall of large listric normal faults emerging along the coastline.…”
Section: Comparison To Natural Examplesmentioning
confidence: 99%